2017
DOI: 10.24297/jaa.v7i2.6092
|View full text |Cite
|
Sign up to set email alerts
|

In Site Net Photosynthesis Measurement of a Plant Canopy in a Single-Span Greenhouse

Abstract: Using newly developed sensor units that were more compact and accurate than earlier units (Takakura et al., 2009), this study was conducted to estimate the net photosynthesis of a plant canopy in a practical greenhouse during plant cultivation. Net photosynthesis and the ventilation flow rate are two unknowns in this greenhouse system, with adequate growth of bitter gourd plants. Environmental conditions related to evapotranspiration from the canopy and CO2 flux from the soil surface were measured respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…It has been demonstrated that using the energy balance equation itself, which is the basis of the Penman-Monteith Equation, is a simpler approach [29] .…”
Section: Evapotranspiration Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that using the energy balance equation itself, which is the basis of the Penman-Monteith Equation, is a simpler approach [29] .…”
Section: Evapotranspiration Sensormentioning
confidence: 99%
“…However, the data obtained for the canopy photosynthesis were scattered because of frequent changes in the ventilation amount. It is presented in Figure 15 that although the main factor affecting net photosynthesis is net solar radiation, other factors such as air temperature, CO 2 concentration, and humidity cannot be neglected [29] .…”
Section: Photosynthesis and Transpiration Measurementmentioning
confidence: 99%
“…They determined the ventilation rate using N2O tracer gas under leakage and a small window aperture (therefore a low ventilation rate). Furthermore, Takakura et al (2017) calculated the canopy photosynthesis based on the CO2 balance and the ventilation rate using the energy balance technique under a high ventilation rate condition. Dieleman et al (2017) conducted plant monitoring based on crop measurement techniques using the Crop Photosynthesis Monitor (for measuring crop photosynthesis) and the CropObserver (for measuring photosynthetically active radiation and fluorescence of a large area of the crop).…”
Section: Measurement Of Photosynthetic Rate In a Greenhousementioning
confidence: 99%
“…Monitoring is required to determine whether the greenhouse climate is suitable to the needs of the crop. Real-time monitoring of net photosynthesis of a plant canopy in a greenhouse is crucial to elucidate and improve plant environments (Takakura et al, 2017). Leaf photosynthesis is measured by determining the CO2 uptake of a leaf using a portable gas exchanger device (Hao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, CO 2 is not particularly reliable for real-time estimation of N of cropped greenhouses, and N 2 O and SF 6 are too expensive to use in commercial greenhouses. By contrast, H 2 O can be used for real-time estimation of N even though the greenhouse contains plants, provided that evapotranspiration rate therein is accurately measured Takakura et al, 2009Takakura et al, , 2017 Nevertheless, there appears to be room for improving accuracy, especially under the conditions where N suddenly changes Takakura, 2017 . The AD models of natural ventilation are based on Bernoulli's principle. They consider that airflow through a vent is caused by the difference between the pressure inside and outside the vent, and that the pressure difference is induced by buoyancy forces so-called stack effect or thermal effect and wind forces wind effect e.g., Kozai et al, 1980;Sase et al, 1980;Boulard and Baille, 1995;Boulard et al, 1996;Kittas et al, 1997 . Using this method, it is possible to estimate N in real time with measured levels of relevant environmental elements, including the difference between the temperature inside and outside the greenhouse for stack effect and wind speed for wind effect , as well as the opening area of vents.…”
Section: Introductionmentioning
confidence: 99%